Conflict detection in a sequential decision task is associated with increased cortico-subthalamic coherence and prolonged subthalamic oscillatory response in the beta band - Patai, EZ; Foltynie, T; Limousin, P; Akram, H; Zrinzo, L; Bogacz, R; Litvak, V (Society for Neuroscience, 2022)
Making accurate decisions often involves the integration of current and past evidence. Here we examine the neural correlates of conflict and evidence integration during sequential decision making. Female and male human patients implanted with deep-brain stimulation (DBS) electrodes and age- and gender matched healthy controls performed an expanded judgement task, in which they were free to choose how many cues to sample. Behaviourally, we found that while patients sampled numerically more cues, they were less able to integrate evidence and showed suboptimal performance. Using recordings of Magnetoencephalography (MEG) and local field potentials (LFP, in patients) in the subthalamic nucleus (STN), we found that beta oscillations signalled conflict between cues within a sequence. Following cues that differed from previous cues, beta power in the STN and cortex first decreased and then increased. Importantly, the conflict signal in the STN outlasted the cortical one, carrying over to the next cue in the sequence. Furthermore, after a conflict, there was an increase in coherence between the dorsal premotor cortex and subthalamic nucleus in the beta band. These results extend our understanding of cortico-subcortical dynamics of conflict processing, and do so in a context where evidence must be accumulated in discrete steps, much like in real life. Thus, the present work leads to a more nuanced picture of conflict monitoring systems in the brain and potential changes due to disease.Significance StatementDecision-making often involves the integration of multiple pieces of information over time in order to make accurate predictions. We simultaneously recorded whole-head magnetoencephalography and local field potentials from the human subthalamic nucleus in a novel task which required integrating sequentially presented pieces of evidence. Our key finding is prolonged beta oscillations in the subthalamic nucleus, with a concurrent increase in communication with frontal cortex, when presented with conflicting information. These neural effects reflect the behavioural profile of reduced tendency to respond after conflict, as well as relate to suboptimal cue integration in patients, which may be directly linked to clinically reported side-effects of Deep Brain Stimulation such as impaired decision-making and impulsivity.